Impact of Tobacco Use and Prevention Laws on Regional Cigarette Sales: An Analysis of Provincial Disparities and Convergence Patterns in Spain - Aida Galiano; Josep Blasco; Juan Manuel Martín-Álvarez; Miguel Angel Del Arco Osuna (Health Economics Review)
Abstract This paper aims to examine regional disparities in cigarette sales that occurred after the implementation of two laws regulating the sale and use of tobacco products in Spain. These laws became effective in December 2005 (Act 28/2005) and December 2010 (Act 42/2010). Furthermore, it provides a framework for studying spill-over effects pertaining to cross-border strategies that may alter how frontier regions react to the implementation of the laws. Provincial official data from January 2005 to December 2010 for legal cigarette sales has been divided into two distinct periods based on these regulatory changes. We apply Phillips and Sul's club convergence test for absolute and withing-group convergence. Our findings indicate that although the 2010 law helped to reduce disparities across provinces, there was no complete convergence, meaning that the impact of the law was not uniform across all regions, especially in frontier regions with France and Gibraltar. However, we observe evidence of convergence within groups of similar entities, and the number of these groups decreased over time. This outcome highlights several interesting insights. Firstly, it supports what previous studies have established, indicating that the 2010 law was more restrictive than the one in 2005. Secondly, the effectiveness of these regulations can vary in border regions due to different laws in neighboring countries, resulting in unintended consequences that can reduce the impact of tobacco control policies, a result that is also in line with the literature. Finally, it is important to have harmonized regulations to ensure greater effectiveness in controlling tobacco use.